TANTANGAN DAKWAH DALAM TRADISI AKKATTERE PADA KOMUNITAS AMMATOWA KAJANG DALAM KABUPATEN BULUKUMBA (Fakultas Dakwah dan Komunikasi, 2020)
The purpose of this research is the challenges of Da'wah in the Akkattere Tradition in the Kajang Dalam Ammatowa Community in Bulukumba Regency. This is Qualitative research using the Da'wah Management approach. The data sources of this research are: first, primary data, namely data obtained from the results of research and observations made in the field where the data was obtained from various communities including customary stakeholder, community leaders, and the local government. Second, secondary data is obtained through a literature review. Them the data collection method used is observation and interview. Then the data analysis technique is carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate that the process of Akkattere tradition is a traditional party in the form of haircutting rituals carried out by the able Ammatowa community, indigenous descendants, and still obedient pairs. Akkattere is considered to be the same as the pilgrimage because it is both done by capable people and both expect the reward from Tu Rie ‘A’ra’na (God) the next day (afterlife).